Analisis Perbedaan Tekanan Fluida pada Ball Valve Kondisi Full Closed dan Full Open dengan Computational Fluid Dynamics - Meri Rahmi; Delffika Canra; Suliono Suliono (P3M Politeknik Negeri Indramayu, 2018)
Ball valve is one type of rotary motion valve. Ball valve functions as a round disc-shaped ball-like controller. Ball valve is widely used because it is easy to repair and the ability in high pressure and high temperature. The fluid flow in the ball valve does not always flow, sometimes the flow is closed. This will affect the fluid pressure in the valve. Fluid pressure is also affected due to valve open condition. This study aims to analyze the difference of the fluid pressure in ball valve -4 inch ANSI during closed condition and open condition. The method used is Computational Fluid Dynamics with f Flow Simulation Solidworks software. The analysis was performed for two valve conditions with a temperature of 425 °C. Decrease in pressure does not significantly affect the condition of the ball valve, even when the temperature of the fluid is high. The difference of fluid pressure between full closed condition and full open is only 0.01 psi.